Genus Lingulops (Lingulata, Brachiopoda) in Silurian of the Barrandian - Mergl,M. (Journal of the Czech Geological Society, 1999)
A new species Lingulops barrandei sp. n. is described from the Kopanina Formation (Ludlow) of the Barrandian. Functional morphology of the genus is discussed.
Keywords: Brachiopoda; Lingulata; Silurian; Barrandian; Czech Republic